Low immune cell ARA and high plasma 12-HETE and 17-HDHA in iron-deficient South African school children with allergy. (July 2016) - Malan, L.; Baumgartner, J.; Calder, P.C.; Smuts, C.M.
Abstract: Allergy has been associated with altered fatty acid and inflammatory status. In this cross-sectional study of 321 rural iron deficient (ID) South African children (aged 6–11 years), a subsample (n=111) of children with parent-reported allergy data were divided into an allergic (n=30) and non-allergic (n=81) group and compared. PBMC arachidonic acid (ARA; P =0.010) and the PBMC ARA to dihomo-gamma-linolenic acid (DGLA) ratio ( P =0.035) were lower in the allergic children. Plasma 12-hydroxyeicosatetraenoic acid and 17-hydroxydocosahexaenoic acid (17-HDHA) were higher ( P =0.040 and 0.020, respectively) in the allergic group. Thus, a fatty acid composition and lipid mediator levels indicative of increased release of ARA from PBMC membranes, increased inflammation as well as the resolving thereof, were associated with parent-reported allergy symptoms. This study used baseline data of an intervention study which was registered at clinicaltrials.gov as NCT01092377. Highlights: Total phospholipid ARA in PBMC was lower in allergic children. Plasma 12-HETE and 17-HDHA were higher in allergic children. A fatty acid composition and lipid mediator levels indicative of increased release of ARA from PBMC membranes, increased inflammation as well as the resolving thereof, were associated with parent-reported allergy symptoms.